Clinical effectiveness of very‐low‐energy diets in the management of weight loss: a systematic review and meta‐analysis of randomized controlled trials. (18th January 2016) - Parretti, H. M.; Jebb, S. A.; Johns, D. J.; Lewis, A. L.; Christian‐Brown, A. M.; Aveyard, P.
Summary: Guidelines suggest that very‐low‐energy diets (VLEDs) should be used to treat obesity only when rapid weight loss is clinically indicated because of concerns about rapid weight regain. Literature databases were searched from inception to November 2014. Randomized trials were included where the intervention included a VLED and the comparator was no intervention or an intervention that could be given in a general medical setting in adults that were overweight. Two reviewers characterized the population, intervention, control groups, outcomes and appraised quality. The primary outcome was weight change at 12 months from baseline. Compared with a behavioural programme alone, VLEDs combined with a behavioural programme achieved −3.9 kg [95% confidence interval (CI) −6.7 to −1.1] at 1 year. The difference at 24 months was −1.4 kg (95%CI −2.6 to −0.2) and at 38–60 months was −1.3 kg (95%CI −2.9 to 0.2). Nineteen per cent of the VLED group discontinued treatment prematurely compared with 20% of the comparator groups, relative risk 0.96 (0.56 to 1.66). One serious adverse event, hospitalization with cholecystitis, was reported in the VLED group and none in the comparator group. Very‐low‐energy diets with behavioural programmes achieve greater long‐term weight loss than behavioural programmes alone, appear tolerable and lead to few adverse events suggesting they could be more widely used than current guidelines suggest.